Ndubueze Ejeh, Benedict. 2025. Persona, errore e dolo nel matrimonio canonico, pp. 184. Venezia: Marcianum Press - Lewandowski, Piotr (Prawo Kanoniczne, 2026)
The reviewed monograph by Benedict Ndubueze Ejeh addresses the questions of a person, error and fraud in the historical perspective and jurisprudence of the Tribunal of the Roman Rota. The author argues that an error regarding a person results from the sexual identity of nupturients, while an error regarding the attribute of a person on the basis of jurisprudence refers to attributes leading to the creation of a community of married life, such as spiritual, religious, social, moral, psychological or deviant attributes. As for fraud, it denies the essence of marriage because it lacks the truth and sincerity which are due to spouses on account of natural law and divine institution, while the legal error regulated in can. 1099 is a false judgment regarding the sacramental nature of marriage of baptized parsons. The monograph does not specify research methods or the state of research. It also lacks summaries of particular chapters and an ending. This publication may be useful for employees of ecclesiastical courts.